Remoteness and remote places. A geographic perspective. (December 2016) - Bocco, Gerardo
Abstract: Remoteness is a complex notion. A remote place implies a distant site with reference to where the one person positing such a qualification is located. However, it would be difficult to indicate how distant or how far a place would be, in order for it to be labeled as remote. The goal of this article is to contribute to the understanding of two components of remoteness: the absolute and the relative dimensions, and to shed light on the framing of remoteness. The premise is that the very notion of remoteness has not disappeared but is continually receiving new meanings. Remoteness has been redefined, re-signified and relocated in our minds and practices.